800 nm Bandwidth Amplified Spontaneous Emission of Divalent Cobalt Ion-doped Fiber Pumped at 550 nm. Issue 4 (2nd October 2018) - Zhang, Chao Min; Wang, Lin Jun; Ji, Xin; Zhu, Peng Fei; Gao, Ya
ABSTRACT: In this work, the energy levels, transition configuration and numerical model of cobalt ion-doped fiber is proposed and analyzed. A three-level system is employed to model the amplified spontaneous emission (ASE) of the doped fiber pumped at 550 nm, and the rate and power propagation equations are solved to analyze the effect of fiber length, active ion concentration, pump power and temperature on the ASE. It is shown that the fiber has an ultra-broadband ASE in 1100-1900 nm range, which will be promising for fiber communication system, fiber sensor and medical imaging. GRAPHICAL ABSTRACT: